The Effect of Ethnolinguistic-Based Experiential Learning Model on Critical Thinking Abilities of PGSD Students - Nuriyanti, Risma; Susilawati; Amelia, Deceni; Gumelar, Abih (Jurnal Profesi Pendidikan, 2025)
The low critical thinking ability of students needs serious attention. This study aims to determine the effect of ethnolinguistically-based experiential learning models on the essential thinking abilities of PGSD students. The research method used is a pre-experiment with a group pretest-posttest design. The population in this study was 6th-semester PGSD students at the Indonesian Education Institute. The sample taken was class 5B, totaling 33 people, with a purposive sample technique. The study yielded an average initial ability value of 79.3 and an increase in the posttest value to 84.18. The results of data analysis showed that the pretest-posttest t value was 0.8 with a probability of 0.00. Therefore, we can conclude that the ethnolinguistic-based experiential learning model influences students' critical thinking abilities.